2017
DOI: 10.1007/s00018-017-2575-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly targeted therapies for p53-mutant cancers

Abstract: The tumor suppressor p53 is lost or mutated in approximately half of human cancers. Mutant p53 not only loses its anti-tumor transcriptional activity, but often acquires oncogenic functions to promote tumor proliferation, invasion, and drug resistance. Traditional strategies have been taken to directly target p53 mutants through identifying small molecular compounds to deplete mutant p53, or to restore its tumor suppressive function. Accumulating evidence suggest that cancer cells with mutated p53 often exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 162 publications
(193 reference statements)
3
51
0
Order By: Relevance
“…Thus, for the two last decades, numerous compounds were identified to destabilize highly accumulated GOF p53 mutants, or to reverse the oncogenic properties of mutp53 ( Figure 1 and Table 1 ) (also reviewed in [ 6 , 7 , 19 , 20 , 63 ]). Besides strategies to directly target stabilized mutp53 for degradation or reactivation by restoring a ‘wild-type-like’ conformation, many approaches are indirect, suggesting to (I) exploit tumor cell vulnerabilities that result from missense mutp53-specific signaling to downstream pathways [ 7 , 20 , 64 ], (II) inhibit the remaining G2 checkpoint on which such tumor cells depend, since wtp53-deficient tumors have lost their G1 checkpoint [ 20 , 64 ], (III) target mutp53-mediated metabolic pathways [ 64 , 65 ] and (IV) inhibit mutp53 interactors that accelerate cancer progression [ 7 , 20 , 64 ].…”
Section: Targeting Mutp53 For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for the two last decades, numerous compounds were identified to destabilize highly accumulated GOF p53 mutants, or to reverse the oncogenic properties of mutp53 ( Figure 1 and Table 1 ) (also reviewed in [ 6 , 7 , 19 , 20 , 63 ]). Besides strategies to directly target stabilized mutp53 for degradation or reactivation by restoring a ‘wild-type-like’ conformation, many approaches are indirect, suggesting to (I) exploit tumor cell vulnerabilities that result from missense mutp53-specific signaling to downstream pathways [ 7 , 20 , 64 ], (II) inhibit the remaining G2 checkpoint on which such tumor cells depend, since wtp53-deficient tumors have lost their G1 checkpoint [ 20 , 64 ], (III) target mutp53-mediated metabolic pathways [ 64 , 65 ] and (IV) inhibit mutp53 interactors that accelerate cancer progression [ 7 , 20 , 64 ].…”
Section: Targeting Mutp53 For Cancer Treatmentmentioning
confidence: 99%
“…This is human-relevant, since the majority of human mutp53 tumors undergo loss-of-heterozygosity (LOH). GOF mutants represent a phenotypic spectrum and depend on tumor context, described in several excellent recent reviews [ 6 , 7 , 16 , 17 , 18 , 19 , 20 ]. Taken together, targeting cancer-associated mutp53 GOF functions is a highly promising rational approach that strikes cancer cells selectively, with low toxicity in healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear at this time whether these will necessarily be mutation specific, or whether drugs can be developed that will destabilize diverse mutant forms. In addition, there has been interest in identifying pathways that become necessary for cell survival in the presence of TP53 mutations, as these could function as synthetic lethality strategies [58]. This may offer an alternative approach, although it will be important to determine whether these strategies result in cell-type specificity or if they might become effective across diverse cancer cell types.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…1). Despite the central role of TP53 in HNSCC carcinogenesis (2), to date no standard-of-care therapy leverages the tumor's p53 status, albeit preclinical work, and clinical trials are bringing this goal closer (3)(4)(5). We have previously found that inhibition of the cell-cycle kinase WEE1 with a small-molecule AZD1775 is significantly more cytotoxic to p53-mutated than to p53 WT HNSCC cell lines (6).…”
Section: Introductionmentioning
confidence: 99%